PENGUJIAN GESER PADA INTERFACE BONDING JOINT HIBRID AL-CFRP DENGAN VARIASI GEOMETRI PERMUKAAN AL - assidiq, maulana hasbi; Wicaksono, Dhimas; Setiawan, Ferry (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Composites are a combination of two or more materials and each has its own properties and characteristics and produces one material with stronger properties than the supporting material. In this study using aluminum, carbon fiber and combined using epoxy resin. This research will produce new material products with variations without surface treatment (TST), HTG, HDG, and 2HDG. The manufacturing process in this study uses the hand lay up method and continues with the vacuum bagging method and is pressed with an iron plate. Shear testing was carried out with the aim of knowing the strength of the specimen against the applied shear force. The results obtained after shear testing of the three TST variations obtained the highest shear stress value in the TST 1 variation of 3.21 MPa and a maximum load of 1141.10 N. Then in the three HTG specimens obtained the highest shear stress value in HTG 1 of 5.54 MPa and 1768.57 N. Then in the three HDG specimens obtained the highest shear stress value in HTG 1 of 5.54 MPa and 1768.57 N. Then in the three HDG specimens, the highest shear value was obtained in HDG 2 of 3.00 MPa and 1005.99 N. Then in the three 2HDG specimens, the highest value was obtained in 2HDG 1 of 2.94 MPa and 1074.59 N. From the test results it is found that the specimen with the HTG variation has a higher shear stress value than the other variations. The type of failure in the kosongan and HTG variation specimens experienced a type of adhesive shear failure and in the HDG and 2HDG variations experienced cohesive shear failure.